Phoenix in Guillermo Reyes’s Places to Touch Him - Foster, David William (Latin American Theatre Review, 2010)
Guillermo Reyes is one of the most important contemporary Chicano dramatists, as much for his ingenious use of language as for his perceptive and unflinching treatment of gay male culture as it affects Chicano men. Reyes is particularly attuned to the urban culture of the American Southwest, and the bulk of his plays focuses on the urban implications of Chicano life, which include issues of gay life. While the majority of Reyes’s plays are set in Los Angeles, which has experienced in recent decades an important accommodation of visible gay life, Reyes’s 2002 play, Places to Touch Him, is situated in the greater Phoenix area, where Reyes lives. Phoenix, while it has a measure of visible gay life, presents significant differences relative to Los Angeles, and this is no more apparent than in the matter of political fortunes for openly gay men (and women). This article discusses how Places engages with the particular parameters of gay life in a U.S. city like Phoenix. (DWF, Article in English)